Responses of the microbial community and the production of extracellular polymeric substances to sulfamethazine shocks in a novel two-stage biological contact oxidation system - Zhou, Jia; Chen, Tian; Cui, Jing; Chen, Yan; Zhao, Shuai; Qu, Jian-Hang; Wang, Zitong; Pan, Jingshi; Fan, Lixin (Frontiers in Microbiology, 2023)
Introduction The biological contact oxidation reactor is an effective technology for the treatment of antibiotic wastewater, but there has been little research investigating its performance on the sulfamethazine wastewater treatment. Methods In this study, a novel two-stage biological contact oxidation reactor was used for the first time to explore the impact of sulfamethazine (SMZ) on the performance, microbial community, extracellular polymeric substances (EPS), and antibiotic-resistant genes (ARGs). Results The chemical oxygen demand (COD) and ammonia nitrogen (NH4+-N) removal efficiencies kept stable at 86.93% and 83.97% with 0.1–1 mg/L SMZ addition and were inhibited at 3 mg/L SMZ. The presence of SMZ could affect the production and chemical composition of EPS in the biofilm, especially for the pronounced increase in TB-PN yield in response against the threat of SMZ. Metagenomics sequencing demonstrated that SMZ could impact on the microbial community, a high abundance of Candidatus_Promineofilum, unclassified_c__Anaerolineae, and unclassified_c__Betaproteobacteria were positively correlated to SMZ, especially for Candidatus_Promineofilum. Discussion Candidatus_Promineofilum not only had the ability of EPS secretion, but also was significantly associated with the primary SMZ resistance genes of sul1 and sul2, which developed resistance against SMZ pressure through the mechanism of targeted gene changes, further provided a useful and easy-implement technology for sulfamethazine wastewater treatment.